Memaknai Substansi Syari’at yang Membebaskan - Yasid Yasid (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2018)
Shari'at is a form of manhaj (method) which is built to give birth to values that are very needed as a reference for human life on this earth. Shari'at is a overreached movement every text and expression as well always work hard with any formed changes whatever happned in society. Therefore, neither all divine revelation texts contain dimension of shari'at at the level of praxis it nor identical with the classic Ulama’s opinion which is created according to the needs of its time. On the contrary, the Shari'ah is the driving force for the style of community dynamism which is inevitably occurs as the movement of the world ball continues to accelerate. Thus, the Shari'ah is not synonymous with the dictums of Istinbath product law or principle of Fiqhiyyah which contains the nomenclature of the Mujtahid's opinions. The other way, the Shari'ah is a mechanism of dialogue between the text of the holy teachings on the a hand and the struggle for social reality on the other. Therefore, Shari'ah at the level of substance is always up-to-date at all times because itself has a mechanical function to update the entire series of changes and developments that occur in the community. Shari'ah is a method that processed creating laws without freezing the law itself. Shari'at is a spirit that continued creating guide lines and rolled out interpretations, updates, anddissolving in the ice of thought.